Development of a Model for the Intention to Purchase Environmentally Friendly Products Through Green Brand Image Mediation: A Case Study of Generation Z in Indonesia - Annida Khoiriani; Arif Triwinarso (Universitas Negeri Semarang, 2026)
This study investigates the influence of green advertising and green product innovation on green brand image and their impact on green purchase intention among Generation Z consumers in Indonesia. Grounded in the Theory of Planned Behavior, the study extends green consumption research by positioning green brand image as a mediating mechanism that connects sustainability-oriented marketing strategies with consumers’ pro-environmental behavioural intentions. Prior TPB-based studies largely emphasize attitudinal and normative determinants, while limited attention has been given to marketing-driven signals, such as green advertising and product innovation in shaping behavioural intention through brand perception, particularly among Generation Z in emerging economies. Using a survey of 250 Generation Z respondents analysed with Structural Equation Modelling, the results show that green advertising and green product innovation significantly strengthen green brand image, which subsequently increases green purchase intention. Green brand image also partially mediates these relationships. The findings refine TPB-based green consumption models by highlighting the strategic role of brand perception in translating sustainability marketing efforts into green purchasing behaviour and provide implications for firms in designing credible green communication and innovation strategies.